The More Things Change, the More They Stay the Same? The Safety Net and Poverty in the Great Recession - Bitler, Marianne; Hoynes, Hilary (Journal of Labor Economics, 2016)
Much attention has been given to the large increases in safety net spending during the Great Recession. We examine the relationship between poverty, the safety net, and business cycles historically and test whether there has been a significant change in this relationship. We find that post–welfare reform, Temporary Assistance for Needy Families did not respond during the Great Recession and extreme poverty is more cyclical than in prior recessions. Food Stamps and Unemployment Insurance are providing more protection—or no less protection—in the Great Recession, and there is some evidence of less cyclicality for 100% poverty.